Analytical study of methods to reduce excavation-induced movements - Aryani, Febrina (2012)
In this project, both two-dimensional and three-dimensional analyses were carried out using the finite element method to evaluate the performance of braced excavation systems in soft clay deposit. Wall systems of different stiffness were considered. Plane Strain Ratio (PSR) is used to compare the two-dimensional wall movement with the three-dimensional wall movement. The results show that plane strain analyses give slightly more conservative estimates of wall movement as compared to three-dimensional analyses. As the excavation length is more than four times the width of the excavation, the PSR is close to unity. In situations where the wall movements are excessive, improvement methods are commonly used to further reduce the wall movements. In this report, two improvement methods are analyzed, namely jet grouting and cross wall system. Several arrangements of the improvement methods are modeled using PLAXIS 3D Foundation software. Eighteen three-dimensional models with varied wall stiffness are considered to find out the optimal improvement method to reduce the wall movement and the maximum strut forces. Comparisons of the wall movements and strut forces from jet grouting and cross walls methods indicate that both improvement methods are effective in reducing both the wall movement and the strut forces. Jet grouting is observed to be more effective in the cases of low stiffness wall systems, while cross wall method is more effective for the higher stiffness wall systems. Walltype jet grouting gives better performance than block-type jet grouting. Block-type jet grouting requires a very large improvement area to be effective and thus is not as economical. Cross walls should be installed at the right positions to restrain the wall movement effectively, i.e. around the area where the maximum wall movement is anticipated.